НЕКОТОРЫЕ БИОГЕОХИМИЧЕСКИЕ ОСОБЕННОСТИ ОЗЕРНЫХ ТЕРМОКАРСТОВЫХ ЭКОСИСТЕМ СУБАРКТИКИ ЗАПАДНОЙ СИБИРИ ПРИ КЛИМАТИЧЕСКИХ ИЗМЕНЕНИЯХ (Eurasian Journal of Ecology, 2016)
In work it is considered some biogeochemical features of lake thermokarstic ecosystems of subarctic region of Western Siberia at climatic changes